Ochrona dzieci – praktyczne doświadczenia ze wsparciem dla rodzin dysfunkcyjnych w Czechach - Fabián, Petr (Humaniora. Czasopismo Internetowe, 2020)
This article is about supporting dysfunctional families, in which children are neglected and parents do not fulfill their parental responsibilities. The whole article is based on the practice of children’s centers, which is based on the principles and processes of deinstitutionalisation in the implementation of social and legal protection of children.